2024
DOI: 10.4314/sajas.v53i3.11
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatments of <i>Mirasolia diversifolia</i> using <i>Lactobacillus bulgaricus</i> at different dosages and fermentation times: Phytic acid concentration, enzyme activity, and fermentation characteristics

R. Pazla,
E.M. Putri,
N. Jamarun
et al.

Abstract: The present study aimed to determine the optimal dosage and fermentation time of Mirasolia diversifolia (leaves and stems) using Lactobacillus bulgaricus bacteria by observing the reduction in phytic acid, the activity of enzymes, pH of fermentation, number of bacterial colonies, and tannin concentration. An experiment was conducted using a completely randomized design (CRD) and 2×3 factorial design with three replications. The treatment factors were Factor A (L. bulgaricus dosages): A1 = 2% (g/v), A2 = 3% (g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Phytase-producing bacteria, which typically generate substantial quantities of phytic acid, can experience a drop in activity when measured at varying time intervals. This issue was noted in the study by Pazla et al, (2023) , where Lactobacillus bulgaricus within Mirasolia diversifolia exhibited a significant reduction in phytic acid content from 21.14 U/ml after one day of fermentation to 5.26 U/ml. Additionally, it was observed that introducing a 3 % concentration of L. bulgaricus to the fermentation of M. diversifolia over a period of five days led to a minimum phytic acid content of 4.30 mg/100 g, indicating a degradation rate of 63.62 %.…”
Section: Discussionmentioning
confidence: 88%
“…Phytase-producing bacteria, which typically generate substantial quantities of phytic acid, can experience a drop in activity when measured at varying time intervals. This issue was noted in the study by Pazla et al, (2023) , where Lactobacillus bulgaricus within Mirasolia diversifolia exhibited a significant reduction in phytic acid content from 21.14 U/ml after one day of fermentation to 5.26 U/ml. Additionally, it was observed that introducing a 3 % concentration of L. bulgaricus to the fermentation of M. diversifolia over a period of five days led to a minimum phytic acid content of 4.30 mg/100 g, indicating a degradation rate of 63.62 %.…”
Section: Discussionmentioning
confidence: 88%